Delayed Ferumoxtran‐10‐Enhanced Magnetic Resonance Neurography of the Lumbosacral Plexus: Impact on Vascular Suppression and Image Quality - Kaniewska, Malwina; Deininger‐Czermak, Eva; Ensle, Falko; Donati, Olivio F.; Guggenberger, Roman (Journal of magnetic resonance imaging, 2025)
Background Intravenous Ferumoxtran‐10 belongs to ultra‐small superparamagnetic iron oxide particles and can be used for magnetic resonance neurography (MRN) as an alternative to other imaging methods which use contrast agents. Purpose To examine the impact of intravenous Ferumoxtran‐10 on vascular suppression and compare image quality to gadolinium (Gd)‐enhanced image acquisition in MRN of lumbosacral plexus (LS). Study Type Prospective. Population/Subjects 17 patients with Ferumoxtran‐10‐enhanced MRN, and 20 patients with Gd‐enhanced MRN. Fieldstrength/Sequence 3T/3D STIR sequence. Assessment Image quality, nerve visibility and vascular suppression were evaluated by 3 readers using a 5‐point Likert scale. Statistical Tests Inter‐reader agreement (IRA) was calculated using intraclass coefficients (ICC). Quantitative analysis of image quality was performed by signal‐to‐noise ratio (SNR) and contrast‐to‐noise ratio (CNR) measurements and compared using Student's t‐testing. Results Image quality, nerve visibility and vascular suppression were significantly higher for Ferumoxtran‐10‐enhanced MRN compared to Gd‐enhanced MRN sequences (p < 0.05). IRA for image quality of nerves was good in Gd‐enhanced and Ferumoxtran‐10 MRN with ICC values of 0.76 and 0.89, respectively. IRA for nerve visibility was good in Gd‐ and Ferumoxtran‐10 enhanced MR neurography (ICC 0.72 and 0.90). Mean SNR was significantly higher in Ferumoxtran‐10‐enhanced MRN for all analyzed structures, while mean CNR was for significantly better for S1 ganglion and femoral nerve in Ferumoxtran‐10‐enhanced MRN (p < 0.05). Data Conclusion Ferumoxtran‐10‐enhanced MRN of the LS plexus showed significantly higher image quality and nerve visibility with better vascular suppression as compared to Gd‐enhanced MRN. Evidence Level 2 Technical Efficacy Stage 3